2002
DOI: 10.1093/toxsci/65.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and Midazolam Act in Combination to Depress Respiration in Rats

Abstract: High dose buprenorphine is used as substitution treatment in human heroin addiction. Deaths have been reported in addicts using buprenorphine, frequently in association with benzodiazepines. In the current study, we observed the effects of buprenorphine and midazolam alone and in combination on arterial blood gases. Four groups of 10 male Sprague-Dawley rats received a parenteral injection of aqueous solvent, buprenorphine (30 mg/kg, iv), midazolam (160 mg/kg, ip), or buprenorphine (30 mg/kg, iv) plus midazola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Animal studies confirmed the potential dangers of the concurrent administration of buprenorphine and benzodiazepines [9,10].…”
Section: Discussionmentioning
confidence: 73%
“…Animal studies confirmed the potential dangers of the concurrent administration of buprenorphine and benzodiazepines [9,10].…”
Section: Discussionmentioning
confidence: 73%
“…The co-ingestion of other drugs in combination with buprenorphine has been postulated as a risk factor by several groups [4][5][6][7][8][9]11,13,45].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, midazolam alone have been shown to express moderate effects on respiration similarly to buprenorphine. However, combined they produced a profound respiratory depression [13]. Thus, one must be cautious to extrapolate findings from one combination to a whole group of drugs even though they are pharmacologically similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catheters were then tunneled subcutaneously and fixed at the back of the neck [20]. The rats were given at least a 24 h recovery period to allow for washout of anesthesia.…”
Section: Animals and Plasma Collectionmentioning
confidence: 99%